Marking place new perspectives on Early Neolithic enclosures - Last, Jonathan (Oxbow Books, 2022)
Intro -- Foreword -- Contents -- List of contributors -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Chapter 12 -- Chapter 13
Falsche Bandangabe auf dem Umschlag: 14
Auf dem Geleitwort: "This book presents the proceedings of a seminar held in November 2019, organised by the Neolithic Studies Group (NSG), that forms part of an ongoing series of NSG seminar papers ..."
Keywords: Wall; Neolithikum; Großbritannien; Electronic books; Konferenzschrift